Photocatalytic reduction of nitrate by a bismuth-based nanostructured photocatalyst - Navarrete Vega, Angélica María (2022)
Nitrate removal is of great importance in water treatment systems due to its negative impacts, from eutrophication to the immediate risk to human health. Photocatalysis has emerged as a promising water treatment process to overcome this problem, because it can use the sunlight to degrade the pollutants. In this context, bismuth oxyiodide photocatalytic microspheres have been synthesized. The products were characterized by XRD, SEM, TEM, EDS and UV-VIS diffuse reflectance spectroscopy. The effect of photocatalyst dosages (i.e., 0.03, 0.06, 0.13 g) on the photocatalytic reduction of nitrate was investigated. The highest photocatalytic reduction was obtained in presence of 0.13 g of BiOI, achieving a reduction percentage of 57% after 3 hours of visible light irradiation. The important role of formic acid as a hole scavenger for the nitrate reduction process was also demonstrated. Different concentrations of formic acid were tested (0.002, 0.004, 0.008 M) and it was observed a highest reduction when the concentration was 0.008 M. These results show that BiOI microspheres can be used as promising visible-light-driven photocatalysts for the degradation of inorganic pollutants, such as nitrate.